Pressure ulcer prevalence across Welsh orthopaedic units and community hospitals: surveys based on the European Pressure Ulcer Advisory Panel minimum data set - James, Jane (Int Wound J, 2010)
The survey used the European Pressure Ulcer Advisory Panel (EPUAP) methodology for the collection of pressure ulcer prevalence data. The orthopaedic survey was conducted across all National Health Service Trusts in Wales between 2 and 6 July 2007 while the community hospital survey covering 25% of all community hospital beds was conducted between 21 April 2008 and 2 May 2008. Data were gathered upon 1196 patients (581, 48·6% within orthopaedic units with 615 located in community hospitals). Of these patients, 81 (13·9%) and 162 (26·7%) had pressure ulcers in orthopaedic and community hospitals, respectively. Where patients presented with multiple pressure ulcers, the most severe pressure ulcer was recorded. Across both surveys, most pressure ulcers were reported to be either category I or II with 91 category I wounds (33 in orthopaedic units and 58 in community hospitals). Severe (categories III and IV) pressure ulcers affected 78 patients (19 in orthopaedic units and 59 in community hospitals). Adoption of the EPUAP pressure ulcer prevalence methods can help achieve consistent data upon pressure ulcer prevalence in different health care organisations and specialities. The adoption of a consistent data collection capture methodology is a clear prerequisite for the compilation of meaningful pressure ulcer prevalence data sets at a national level.